Differences in self-concept between gifted and non-gifted students: A meta-analysis from 2005 to 2020 - Infantes-Paniagua, Álvaro; Fernández-Bustos, Juan Gregorio; Palomares Ruiz, Ascensión; Contreras-Jordán, Onofre R. (Anales de Psicología / Annals of Psychology, 2022)
Gifted students (i.e., those who are more likely to achieve extraordinary goals in one or more domains) generally differ from the non-gifted students in some of the dimensions of self-concept (i.e., a person’s perception of him/herself). However, the current research on giftedness has evolved to introduce new possible moderators of these differences so it has become necessary to carry out an update on the topic. The aim of the present meta-analysis (reference: CRD42018094723) was to synthesise the studies since 2005 on differences in self-concept between gifted and non-gifted students. The results showed that gifted students have higher levels of general and academic self-concept, especially in math self-concept. However, no differences were found in behavioural and emotional self-concepts, and only slightly lower scores in social self-concept. In physical self-concept they scored significantly lower than non-gifted students. The differences in this sub-dimension are moderated by identification procedures, geographical area, and age, so it is suggested that social stereotypes about giftedness as well as physical activity habits may be some of the reasons for these differences.